Single-cell RNA sequencing reveals roles of unique retinal microglia types in early diabetic retinopathy - Yan Wang; Xiongyi Yang; Yuxi Zhang; Libing Hong; Zhuohang Xie; Wenmin Jiang; Lin Chen; Ke Xiong; Siyu Yang; Meiping Lin; Xi Guo; Qiumo Li; et al. (Diabetology & Metabolic Syndrome, 2024)
Abstract Background The pathophysiological mechanisms of diabetic retinopathy (DR), a blinding disease, are intricate. DR was thought to be a microvascular disease previously. However, growing studies have indicated that the retinal microglia-induced inflammation precedes microangiopathy. The binary concept of microglial M1/M2 polarization paradigms during inflammatory activation has been debated. In this study, we confirmed microglia had the most significant changes in early DR using single-cell RNA sequencing. Methods A total of five retinal specimens were collected from donor SD rats. Changes in various cells of the retina at the early stage of DR were analyzed using single-cell sequencing technology. Results We defined three new microglial subtypes at cellular level, including two M1 types (Egr2 + M1 and Egr2 − M1) and one M2 type. We also revealed the anatomical location between these subtypes, the dynamic changes of polarization phenotypes, and the possible activation sequence and mutual activation regulatory mechanism of different cells. Furthermore, we constructed an inflammatory network involving microglia, blood-derived macrophages and other retinal nonneuronal cells. The targeted study of new disease-specific microglial subtypes can shorten the time for drug screening and clinical application, which provided insight for the early control and reversal of DR. Conclusions We found that microglia show the most obvious differential expression changes in early DR and reveal the changes in microglia in a high-glucose microenvironment at the single-cell level. Our comprehensive analysis will help achieve early reversal and control the occurrence and progression of DR.